On Doctoring: Essays on Professionalism - Jeffrey Spike (Association of American Medical Colleges, 2008)
Abstract This lesson plan uses six non-fiction essays available for free to all U.S. medical students in the book On Doctoring, which is available from the Robert Wood Johnson Foundation. Facilitators should assign the readings a few months in advance, so that all clinical students and residents can complete them in time. Facilitators then meet with the students in a small-group format where the papers are discussed. Each paper takes about 20 minutes to discuss. It is recommended that groups be kept no larger than six or eight to encourage everyone to speak up and to not feel inhibited. This class session has been used for 4 years with third-year medical students. It has always been very well received. It helps that all the stories are written by doctors, and it addresses concerns the students will themselves face someday. Most attempts at reflective exercises founder from being too touchy-feely, or too poorly described. This lesson succeeds because it avoids these pitfalls. The students learn by seeing the mistakes of others who are imperfect human beings like themselves, rather than feeling exhorted by self-appointed saints. This results in much less resistance and much more lively discussion.